Yurchenko I.V. On the existence of optimal control for stochastic differential functional equations under the influence of external disturbances. I. Comparison theorem // ScientificWorld Journal.– 2025.– Iss.30.– Part 2.– P.138–146. - Yurchenko, Igor Valeryjovych (International Scientific Periodical Journal "SWorldJournal" published by: SWorld & D.A. Tsenov Academy of Economics, Svishtov, Bulgaria., 2025)
The article discusses the comparison theorem for solutions of stochastic differential functional equations under the influence of external disturbances and its application to one problem of stochastic control.
The article discusses the comparison theorem for solutions of stochastic differential functional equations under the influence of external disturbances and its application to one problem of stochastic control. У статті розглянуто теорему порівняння для розв'язків стохастичних диференціально-функціональних рівнянь під дією зовнішних збурень та її застосування для однієї задачі стохастичного керування.
Keywords: comparison theorem; stochastic control; stochastic functional differential equations